Nicotinic Acid and its Derivatives: Synthetic Routes, Crystal Forms and Polymorphs - Zhou, Pan-Pan; Sun, Xiao-Bo; Qiu, Wen-Yuan (Current Drug Discovery Technologies, 2014)
Nicotinic acid is a well-known pharmaceutical in the vitamin B group that has attracted great interest in the past decades due to its significant importance in the treatment of the human diseases like pellagra. Also, nicotinic acid derivatives have been devoted to much attention due to their different pharmaceutical effects in the treatment of diseases. In view of this, the developments of nicotinic acid and its derivatives including their synthetic methods by using different substrates, and their structural modifications (e.g., substitution of one or more positions of pyridyl ring or acid) were reviewed in details. Drug molecules like nicotinic acid and its derivatives may exist in more than one crystal form in its solid state, known as polymorphs. Different polymorphs have different dissolution rates and aqueous solubility. Therefore, we reviewed structures of different crystal forms of nicotinic acid and its derivatives.
Keywords: Crystal forms